The Improving Knowledge and Oral Health Behaviour of Cadres through the Use of Dental Care Application - Purnomowati, Ratnasari Dyah; Prasetiowati, Lies Elina; Arianto, Arianto; Linasari, Linasari; Nanda, Gustina Tri (Dental Therapist Journal, 2023)
The limitations of dental healthcare personnel to reach the entire population necessitate the involvement of health cadres in fostering self-care practices for oral health. Through training using the Dental Care Application, they can effectively convey this knowledge to the community. This research aims to enhance the knowledge, attitudes, and actions of Posyandu cadres related to dental and oral health. The research method employed is a Quasi-Experiment with a Non-Randomized Control Group Pretest-Posttest design. The Wilcoxon test is utilized to assess the impact of the Dental Care Application on these variables. The research results indicate a significant increase in knowledge by 96%, attitudes by 98%, and cadre actions by 86%. It is concluded that cadre training using the Dental Care Application positively influences cadre behavior in the context of dental and oral health, with a significant p-value of 0.000. Recommendations for future research include the development of this application for online accessibility and the addition of more diverse features to enhance training effectiveness.